The Slovak Theorists of Central European Integration - Halász, Iván (Great Theorists of Central European Integration, 2023)
The study focuses on four Slovak thinkers and politicians who were involved in various forms of Central European cooperation during the 19th and 20th centuries. Most of the Slovak concepts of integration, which did not start from Slavic solidarity alone and had a broader European context, focused on Central Europe. Therefore, the ideas of Central European and European cooperation have traditionally coincided in Slovakia. The theorists considered were either practising politicians who held high governmental or ministerial positions (Milan Hodža, Milan Rastislav Štefánik), professional diplomats (Štefan Osuský), and those who were active only in the field of political journalism and national movement organisation (Ján Palárik). The majority of these thinkers also had emigrational experiences during the two world wars. The paper first describes their familial, social and religious backgrounds, before discussing their political views and specific actions. It concludes by outlining their common and divergent features, as well as their practical achievements and impact on Slovak public life.KEYWORDS: Central Europe, confession, cooperation, integration, nation, politics